Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Grabfood Di Layanan Aplikasi Grab Di Kota Bandung - Try Oktora Akbar (Jurnal Riset Mahasiswa, 2023)
This study to determine how much influence the service quality and price have on customer satisfaction. The research method used is descriptive and verification methods. The descriptive method in this research is used to find out how service quality, price and customer satisfaction at Grabfood in the Grab application service in Bandung City. While the verification method in this study is used to test the truth of the hypothesis in order to determine the effect of service quality on customer satisfaction at Grabfood in the Grab application service in Bandung City. From this research, it is known that the results of multiple regression analysis show that there is an influence between the variables of service quality and price on customer satisfaction which is systematically stated by statistics. The result of multiple correlation analysis shows that the value of R is included in a strong relationship between the variables of service quality, price and customer satisfaction.